Análise econômica do cultivo do camarão-da-amazônia para os mercados de iscas vivas e juvenis no pantanal do brasil - Valenti, Wagner Cotroni [UNESP]; de Arruda Hayd, Liliam; Vetorelli, Michelle Pinheiro; Martins, Maria Inez Espagnoli Geraldo [UNESP] (My University, 2011)
The implementation of a hypothetical aquaculture facility with hatchery, nursery and grow-out earthen ponds for raising the Amazon River Prawn Macrobrachium amazonicum in the Pantanal was considered. Eight larviculture cycles per year were projected: four to produce post-larvae for stocking in grow-out bait ponds, and four to stock nursery tanks to sell juveniles as seed to growout farms, which produce prawns for human consumption. Annual production would be 146,880 dozen bait prawns and 2,938 thousand juveniles. The assumed sale prices were US$ 1.38 per dozen baits and US$ 15.39 per thousand juveniles. The net present value was US$ 555,890.79, internal rate of return was 48% per year, payback period was 2.4 years and benefit-cost ratio was 3.90. The breakeven price to cover total costs per dozen baits was US$ 0.70 and per thousand juveniles was US$ 17.00, indicating that the selling price assumed for juveniles in base scenario is not realistic. Net return was US$ 84,773.80. The results indicate that this activity would be a lucrative and attractive investment in the Pantanal.
Economic analysis of amazon river prawn farming to the markets for live bait and juveniles in pantanal, brazil
Keywords: Economic indicators; Freshwater prawn; Macrobrachium amazonicum; Prawn; Production cost; South america